Articulated motion and deformable objects : second International Workshop, AMDO 2002, Palma de Mallorca, Spain, November 21-23, 2002 : proceedings - AMDO ( 2002: Palma de mallorca, Spain); Perales, Francisco Jose, 1962-; Hancock, Edwin R. (Berlin : Springer, 2002)
20